Informatica umanistica Risorse e strumenti per lo studio del lessico dei beni culturali - ZOTTI, VALERIA; Pano Alaman, Ana (Strumenti per la didattica e la ricerca, 2017)
From a perspective of great scientific and didactic relevance, the volume is part of today's theoretical-methodological reflections on humanistic computer science and digital humanities, dealing with different aspects of the application of digital technologies to the study of the language of art. The contributions, arising from the research project Lessico multilingue dei Beni Culturali (Multilingual lexicon of cultural heritage), conducted by the University of Florence in collaboration with other Italian and foreign universities, describe numerous online resources and platforms for communication, organization and sharing of applications and data, extremely useful for scholars of vocabulary and specialized translation in multiple languages, in particularly in the field of cultural and artistic heritage.